2005
DOI: 10.1158/1055-9965.epi-04-0919
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Over-the-Counter Sales of the Nicotine Patch and Nicotine Gum on Smoking Cessation in California

Abstract: The Food and Drug Administration approved over-thecounter (OTC) sale of nicotine gum and nicotine patches in 1996. We used data from the 1996 California Tobacco Survey to compare the rates of nicotine replacement therapy (NRT) use and smoking abstinence in California for each month during a period immediately preceding and immediately following the OTC availability of nicotine gum and patches. For smokers eligible to report a quit attempt, the proportion making a quit attempt using NRT and the proportion remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
22
2
Order By: Relevance
“…We modeled the rate of quit attempts and smoking abstinence for each month for a period of time preceding and following the increases in cigarette prices in California, while controlling for the potential confounding influences of recall bias (Gilpin and Pierce 1994), the increase in quits observed following the availability of OTC NRT (Reed et al 2005), and the increase in quitting behavior typically observed each January resulting from New Year's resolutions (Gritz et al 1988;Norcross et al 1989)…”
Section: Abstract Cigarette Price Smoking Cessation Smoking Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…We modeled the rate of quit attempts and smoking abstinence for each month for a period of time preceding and following the increases in cigarette prices in California, while controlling for the potential confounding influences of recall bias (Gilpin and Pierce 1994), the increase in quits observed following the availability of OTC NRT (Reed et al 2005), and the increase in quitting behavior typically observed each January resulting from New Year's resolutions (Gritz et al 1988;Norcross et al 1989)…”
Section: Abstract Cigarette Price Smoking Cessation Smoking Behaviormentioning
confidence: 99%
“…We calculated the proportion of smokers reporting a quit attempt (successful or unsuccessful) for each month from October 1995 to November 1996 and from September 1998 to October 1999 (see Reed et al 2005 for a detailed description). For each calendar month of the survey administration, we calculated a separate quit attempt and abstinence rate for the 10-month interval spanning 2 to 12 months prior to the month in which the survey data were collected.…”
Section: Calculation Of Quit Attempts and Abstinence By Calendar Monthmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not originally a focus of the study, secondary analyses examined the relations of medication use with outcome because of conflicting findings about the effects of cessation medication in real-world contexts (e.g., Pierce and Gilpin, 2002;Reed, Anderson, Vaughn, & Burns, 2005). In our study, participants were not offered cessation medication but 72 of the 278 participants completing the 1-month follow-up reported using cessation medication.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the transient increase in utilization that marks many new prescription medications, this increased utilization appears to have been sustained [14], perhaps because of promotional campaigns. The increased utilization inferred from sales data has since been confirmed in population surveys [15][16][17] (though Table 1 Arguments for and against the Rx-to-OTC switch of NRT…”
Section: Need To Increase Access and Utilizationmentioning
confidence: 91%